Older age onset of systemic sclerosis – accelerated disease progression in all disease subsets. (24th April 2020) - Moinzadeh, Pia; Kuhr, Kathrin; Siegert, Elise; Mueller-Ladner, Ulf; Riemekasten, Gabriela; Günther, Claudia; Kötter, Ina; Henes, Jörg; Blank, Norbert; Zeidler, Gabriele; Pfeiffer, Christiane; Juche, Aaron; et al.
Abstract: Objectives: Systemic sclerosis is a heterogeneous, multisystem disease. It can occur at any age, but most patients develop the disease between the age of 40 to 50 years. There is controversial evidence on whether/how the age at disease onset affects their clinical phenotype. We here investigate the relationship between age at disease onset and symptoms in a large cohort of SSc patients (lcSSc, dcSSc and SSc-overlap syndromes). Methods: Clinical data of the registry of the German Network for Systemic Scleroderma including 3281 patients were evaluated and subdivided into three age groups at disease onset (<40 years, 40–60 years, >60 years). Results: Among all SSc patients, 24.5% developed their first non-Raynaud phenomenon symptoms at the age <40 years, and 22.5% were older than 60 years of age. In particular, older patients at onset developed the lcSSc subset significantly more often. Furthermore, they had pulmonary hypertension more often, but digital ulcerations less often. Remarkably, the course of the disease was more rapidly progressing in the older cohort (>60 years), except for gastrointestinal and musculoskeletal involvement. No significant difference was found for the use of corticosteroids. However, significantly, fewer patients older than 60 years received immunosuppressive treatment. Conclusion: In this large registry, ∼25% of patients developed SSc at an age above 60 years with an increased frequency of lcSSc. In this age group, an onset of internal organ involvement was significantly accelerated across all three subsets. These findings suggest that, in the elderly cohort, more frequent follow-up examinations are required for an earlier detection of organ complications.